BEBERAPA JENIS KERANG KIJING (SUKU: UNIONIDAE) DAN KEONG DI TEPI PERAIRAN SUNGAI RENGAS DAN SUNGKAI, PROPINSI JAMBI - MARWOTO, RISTIYANTI M. (Research Center for Biology-Indonesian Institute of Sciences, 1987)
RISTIYANTI M.MARWOTO. 1987.Some fresh water mussels family L'nionidae and gastropods from Rengas and Sungkai Rivers in Jambi province. Berita Biologi 3(7): 306 -309.Four species of unionids were found in Rengas river; of these Pseudodon vondenbuschianus,Contradens ascia dimotus,Ctenodesma sp.and Rectidens gracilis,while Physunio superbus and C. ascia dimotus were found in Sungkai river.The density of p.superbus was higher than the other species (7 ind/0.09 m ),it seems was affected by the organic detritus and the differences of the substratum sediment.Some of P.superbus were mature with many eggs and glochidia larvae inside the outer gills.The length of this mature mussels is 28 - 56 mm, while the average is 52 mm.The difficulties in finding young Union idae may be due to their size is relatively small it was or caused by the specific biology of these animals.The occurance of some gastropods in Rengas and Sungkai river were also discussed.